Influence of Inulin on Gut Microflora and Mineral Excretion among Formula-Fed Infants - Yap, Keng Wai (2005)
Inulin, also known as fructooligosaccharide is increasingly used in human food preparations. In vitro they have been shown to selectively stimulate the growth of Bifidobacterium as well as mineral absorption. Hence, the present study was designed to investigate the effects of three different concentrations of inulin in 36 healthy formula-fed infants aged between 6 and 12 months. A complete randomised design was used to investigate the bifidogenic effect of inulin in enhancing mineral absorption, namely, calcium, iron, magnesium, zinc and copper. The formula-fed infants were grouped into three groups where they received 0.75 g/d, 1.00 g/d and 1.25g/d, while another group of infants acted as control. All the bifidobacteria faecal isolates were tested and characterised using biochemical test and API20, a genus level test kit. The balance method was opted for mineral balance study. Total blood cholesterol levels were determined to investigate the correlation between inulin intake and total cholesterol level in healthy infants. All the three concentrations of inulin studied were found to significantly (P < 0.05) promote Bifidobacterium growth by inhibiting potential pathogenic microorganisms. With 1.25 g/d of inulin, a significant (P < 0.05) decline in Gram-positive cocci and coliform counts and a significant (P < 0.05) increase in Bifidobacterium count were observed. The increase in inulin consumption also exhibited a greater significant (P < 0.05) difference in pH value. Higher production of short-chain fatty acids as a result of colonic fermentation was observed and therefore, contributing to the reduction of colonic pH. The inulin supplementation has significantly (P < 0.05) improved the absorption of Fe and Mg while no significant (P > 0.05) improvement of the absorption of calcium, copper and zinc were observed. The total cholesterol level was not affected by the three levels of inulin supplementation.